Effects of Irrigation with Treated Slaughterhouse Effluent and Bradyrhizobium spp. Inoculation on Soybean Development and Productivity: Strategies for Sustainable Management - Ana Carolina Murad Lima; Lisiane Brichi; Lucas Renato Trevisan; André Leão de Souza Dominguez; Gustavo Nocera Santiago; Tamara Maria Gomes; Fabrício Rossi (Agronomy)
Water scarcity challenges in agriculture are prompting the exploration of alternative irrigation sources, including treated effluents. This study investigates the effects of irrigation with treated slaughterhouse effluent on soybean productivity and development, with and without inoculation, over two cropping cycles. Plant performance was significantly influenced by environmental factors and the interaction between effluent and inoculation. Plant height and leaf area were greater in the second cycle, with effluent enhancing growth and foliar development. Fresh and dry shoot biomass showed significant interactions among cycle, inoculation, and effluent, with higher effluent concentrations combined with inoculation being most effective in the first cycle. Foliar nitrogen concentrations were higher in the first cycle, particularly at elevated effluent doses, while foliar sodium showed a positive correlation with nitrogen and a negative correlation with magnesium. Chlorophyll indices varied across developmental stages, with maximum chlorophyll b estimated at 85.35% effluent irrigation. Soybean yield did not vary significantly with effluent dilutions, suggesting environmental factors had a greater influence. In conclusion, treated effluent irrigation represents a sustainable strategy for soybean production, optimizing water and nutrient use while reducing reliance on chemical fertilizers.